UPAYA GURU PAI DALAM MENANAMKAN NILAI-NILAI KEJUJURAN PADA SISWA MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD IT BUMI SHOLAWAT WATES - Jannah, Miftahul; As'ari, Hasyim; Aisyah, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the efforts of Islamic Education (PAI) teachers in instilling honesty values in students and to identify the supporting and inhibiting factors. The research employs a qualitative approach with a descriptive design conducted at SD IT Bumi Sholawat Wates. The research subjects include PAI teachers, the principal, and fifth-grade students, selected through purposive sampling techniques. Data collection techniques consist of observation, in-depth interviews, and documentation, while data analysis is carried out through data reduction, data display, and conclusion drawing, with triangulation used to ensure data validity. The findings indicate that the efforts of PAI teachers in instilling honesty values are implemented through integrated strategies, including role modeling, habituation, providing advice, supervision, and the application of sanctions. Role modeling emerges as the most dominant strategy as it provides concrete examples that are easily imitated by students, while habituation strengthens the internalization of values through daily practices. The success of instilling honesty values is supported by a religious school environment and institutional support; however, it is still challenged by external environmental influences and low personal awareness among students. This study emphasizes the importance of the teacher’s role as a role model and highlights the need for synergy between schools, families, and communities in fostering students’ honesty character in a sustainable manner.